Characteristics of Small Bowel Polyps Detected in Cowden Syndrome by Capsule Endoscopy. (24th June 2015) - Saito, Keita; Nomura, Eiki; Sasaki, Yu; Abe, Yasuhiko; Kanno, Nana; Mizumoto, Naoko; Shibuya, Rika; Sakuta, Kazuhiro; Yagi, Makoto; Yoshizawa, Kazuya; Iwano, Daisuke; Sato, Takeshi; et al.
Abstract : Cowden syndrome is an uncommon, autosomal dominant disease characterized by multiple hamartomas and hyperplastic lesions in the skin, mucous membrane, brain, breast, thyroid, and gastrointestinal tract. About 30% of Cowden syndrome cases are reportedly complicated by malignant diseases. Hamartomatous polyps occur throughout the gastrointestinal tract, the most common sites being the stomach, colon, esophagus, and duodenum. Small bowel polyps can occur in Cowden syndrome; however, they are difficult to detect by conventional examination, including double-contrast X-ray study. Here, we report three cases of Cowden syndrome with small bowel polyps, which were detected by capsule endoscopy. The small bowel polyps of Cowden syndrome frequently occur at the oral end of the small bowel, especially in the duodenum and jejunum, and their color is similar to that of the surrounding mucosa; additionally, the polyps are relatively small (2–5 mm). Capsule endoscopy is useful for detecting small bowel polyps in Cowden syndrome.